Torsion of giant ovarian cyst in postmenopausal woman: a case report with review of literature - Hota, Basanta M.; Prashanthi, C. Gowri; Geetha, Lokam; Maneesha, Kurapati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Torsion of ovarian cyst, an acute gynecological emergency, needs attention not only for pain relief but to prevent its serious complications and in certain cases, to preserve the ovary. Though many factors predispose to the pathology, an enlarged ovary is the primary factor in the pathophysiology of torsion. It is rare in postmenopausal women. The Clinical presentation may be variable depending on the extent of pathology, as well as the investigation reports. Ultrasonography, using both grayscale and doppler imaging, and both transabdominal and transvaginal approaches, is the primary diagnostic investigation for patients with clinical suspicion. Surgery is both diagnostic and the treatment of choice. The earlier the treatment, the better the outcome, as it helps prevent complications. In certain cases, the ovary may be preserved through cystectomy and oophoropexy. Torsion of a benign giant ovarian cyst of 24 cm and weighing 3.5 kg in a postmenopausal woman is rare. In our case, a 46 years old postmenopausal parous lady presented with moderate pain abdomen and was found to have a giant ovarian cyst with mild tenderness, diagnosed as 7200 torsions of the right ovarian cyst of 24×20 cm on exploratory laparotomy. Total abdominal hysterectomy with right salpingo-oophorectomy and left salpingectomy was executed considering her age, healthy looking left ovary, and the benign features of the right ovarian cyst. Histopathology revealed a benign mucinous cystadenoma. Her post-operative period was uneventful, and she was found asymptomatic and healthy on follow up.